Does perioperative opioid infusion increase postoperative opioid requirement? - (:unkn) unknown (KARE PUBL, 2015)
Objectives: Opioids are the cornerstone therapy for the optimal pain management. Perioperative opioid infusion is accused of causing acute opioid tolerance, especially as the postoperative opioid requirement increases in time to provide efficient analgesia. It is debatable whether there is a difference between opioid agents regarding tolerance development. We aim to compare the effects of morphine, remifentanil and alfentanil when infused intravenously during the perioperative period. Methods: Sixty patients undergoing elective major abdominal surgery were randomized into four groups. The four groups obtained the following treatments: saline 5 cc iv bolus and 10 cc/h infusion for induction and maintenance in Group C, remifentanil infusion 0.25 mu g/kg/min following 1 mu g/kg iv bolus in Group R, alfentanil infusion 0.50 mu g/kg/min following 10 mu g/kg iv bolus in Group A, and morphine infusion 0.02 mg/kg/h after 0.1 mg/kg iv bolus in Group M. Meperidine 10 mg/cc iv patient-controlled analgesia was used postoperatively, and total meperidine consumptions were recorded. VAS scores and side effects were recorded during postoperative 48 hours. Results: VAS scores in Group M were found to be significantly lower than in Group C at the 1st postoperative hour. Twenty-four hour total meperidine consumption in Group R and Group M were significantly lower than in Group C. No statistical difference was found between groups regarding the incidence of nausea and vomiting. Conclusion: Our study indicated that infusions of morphine, alfentanil and remifentanil administered to patients undergoing major abdominal surgery did not cause acute opioid tolerance. In contrast, infusion of morphine and remifentanil reduced postoperative opioid requirement.
Keywords: Analgesia; continuous infusion; opioids; tolerance; MINIMUM ALVEOLAR CONCENTRATION; SMALL-DOSE KETAMINE; ACUTE TOLERANCE; SEVOFLURANE ANESTHESIA; REMIFENTANIL INFUSION; INDUCED HYPERALGESIA; ANALGESIC TOLERANCE; MORPHINE-TOLERANCE; RAPID DEVELOPMENT; RATS